2021
DOI: 10.1002/hec.4230
|View full text |Cite
|
Sign up to set email alerts
|

The effect of accidents on labor market outcomes: Evidence from Chile

Abstract: We estimate the causal effect of accidents on employment and earnings among Chilean men using event study methods and monthly administrative data. An accident of any type reduces the probability of being employed by 8.4 percentage points in the first year, by 11.2 percentage points in the second year, and by 14.8 percentage points in the third year after the accident. On average, over the three years after the accident, employment declines by 14%, relative to the pre-accident mean. In addition, accidents reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This also assumes that the sick individual will eventually substantially reduced labor supply (and therefore income) or stop all together when the individual needs to qualify for medical care. This is consistent with the consensus in the literature that health shocks reduce labor supply and earnings (e.g., seeLenhart 2019 andParro andPohl 2021).…”
supporting
confidence: 92%
“…This also assumes that the sick individual will eventually substantially reduced labor supply (and therefore income) or stop all together when the individual needs to qualify for medical care. This is consistent with the consensus in the literature that health shocks reduce labor supply and earnings (e.g., seeLenhart 2019 andParro andPohl 2021).…”
supporting
confidence: 92%
“…Fourth, our work relates to the literature on the impact of health shocks on individuals' labor market outcomes (Gallipoli and Turner, 2011;Crichton et al, 2011;Heinesen and Kolodziejczyk, 2013;Halla and Zweimüller, 2013;García-Gómez et al, 2013;Turner and Gallipoli, 2013;Dobkin et al, 2018;Parro and Pohl, 2021;Fadlon and Nielsen, 2021, among many others). This literature generally estimates negative effects of health shocks on employment and earnings, although the estimates vary, partly due to the different types of shocks analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…andLenhart (2019) study the effects of a deterioration of self-reported health status Garcia-Gomez et al (2013),Lundborg et al (2015). andDobkin et al (2018) analyze the effects of acute hospitalization, while Moller Dano (2005),Crichton et al (2011),Halla and Zweimüller (2013) andParro and Pohl (2021) look at the impact of accidents and injuries Moran et al (2011),Heinesen and Kolodziejczyk (2013). andJeon (2016) investigate the effects of surviving cancer.…”
mentioning
confidence: 99%